2021
DOI: 10.3390/ijms22168988
|View full text |Cite
|
Sign up to set email alerts
|

Putative Role of Vitamin D for COVID-19 Vaccination

Abstract: Severe acute respiratory syndrome coronavirus 2 is a new, highly pathogenic virus that has recently elicited a global pandemic called the 2019 coronavirus disease (COVID-19). COVID-19 is characterized by significant immune dysfunction, which is caused by strong but unregulated innate immunity with depressed adaptive immunity. Reduced and delayed responses to interferons (IFN-I/IFN-III) can increase the synthesis of proinflammatory cytokines and extensive immune cell infiltration into the airways, leading to pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 117 publications
(153 reference statements)
0
53
0
1
Order By: Relevance
“…In general, it has been demonstrated that vitamin D induce antimicrobial peptides and mediates anti-inflammatory, antiviral, apoptotic, and autophagic activities [ 6–9 , 17 , 30 ]. The protective immuno-modulatory effects of this fat-soluble steroid vitamin have been reported in respiratory diseases [ 31 , 32 ] including its role in enhancing immune responses to COVID-19 vaccines [ 19 , 20 ]. Studies have proposed vitamin D deficiency as leading candidate in association with COVID-19 susceptibility, severity, and progression [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it has been demonstrated that vitamin D induce antimicrobial peptides and mediates anti-inflammatory, antiviral, apoptotic, and autophagic activities [ 6–9 , 17 , 30 ]. The protective immuno-modulatory effects of this fat-soluble steroid vitamin have been reported in respiratory diseases [ 31 , 32 ] including its role in enhancing immune responses to COVID-19 vaccines [ 19 , 20 ]. Studies have proposed vitamin D deficiency as leading candidate in association with COVID-19 susceptibility, severity, and progression [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…While strong observational evidence [ 11–16 ] indicate the association of low vitamin D levels to the COVID-19 susceptibility, severity, and mortality outcomes, the beneficial use of vitamin D supplements in COVID-19 has been reported in some non-randomized observational cohorts [ 17 , 18 ]. Vitamin D supplementation has also been suggested as a putative useful tool to enhance immune responses to COVID-19 vaccines [ 19 , 20 ]. However, there is still a scarcity of information through randomized controlled trials (RCTs) on the use of vitamin D supplementation in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying rationale for improving the vitamin D status as a preventive or therapeutic measure in the fight against SARS-CoV-2 is based on the multiple interactions of vitamin D with cells of the innate and adaptive immune system [ 7 , 8 , 9 ]. In addition to the immune system, protective effects of vitamin D are also described on ACE2 expression and the renin-angiotensin system (RAS) [ 10 ]. The experimental findings are supported by a number of successful clinical studies, which overall contribute to the high regard for vitamin D as a promising supplement in prevention and a meaningful adjuvant in the treatment of COVID-19 [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D repletion is purported to reduce the risk of infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) 1,2 , mitigate severity of coronavirus disease 2019 (COVID-19) 3 and accelerate recovery 4 . Sufficient serum total 25-hydroxyvitamin D (25D) is postulated to potentiate COVID-19 vaccine effectiveness 5 , boost innate and control adaptive immunity 6,7 , and reduce post-infection cytokine storm 6 and lung injury 8 . A serum 25D level of approximately 50 ng/mL is proposed as the theoretical threshold for zero mortality from COVID-19 based on regression analysis of decreasing deaths rates with rising serum 25D levels 9 .…”
Section: Introductionmentioning
confidence: 99%